Brown Adipose Transplantation Improves Polycystic Ovary Syndrome-Involved Metabolome Remodeling - Yao, Lihua; Wang, Qin; Zhang, Runjie; Wang, Xingyun; Liu, Yiwen; Di, Fangfang; Song, Liwen; Xu, Siliang (Frontiers in Endocrinology, 2021)
Polycystic ovary syndrome (PCOS) is a complex reproductive, endocrine and metabolic disorder in reproductive-age women. In order to explore the active metabolites of brown adipose tissue (BAT) transplantation in improving the reproductive and metabolic phenotypes in PCOS rat model, the metabolites in recipient’s BAT were explored using liquid chromatography-mass spectrometry technique. Totally, 9 up-regulated and 13 down-regulated metabolites were identified. They were roughly categorized into twelve distinct classes, mainly including glycerophosphoinositols, glycerophosphocholines and sphingolipids. Ingenuity pathway analysis predicted these differentially metabolites mainly target to PI3K/AKT, MAPK and Wnt signaling pathways, which were tightly associated with PCOS. Furthermore, one of these differential metabolites, sphingosine belonging to sphingolipids, was randomly selected for further experiments on a human granulosa-like tumor cell line (KGN). It significantly accelerated the apoptosis of KGN cells induced by dihydrotestosterone. Based on these findings, we speculated that metabolome changes are an important process for BAT transplantation in improving PCOS, it might be a novel therapeutic target for PCOS treatment.